Experimental turbulent mixed convection behind a heated cylinder - Boirlaud, Matthieu; Couton, Dominique; Plourde, Frédéric (Journal of physics. Conference series, 2012)
Turbulent mixed convection around a horizontal cylinder at constant temperature exposed to a cross-flow is experimentally investigated by means of flow visualizations, 2D particle image velocimetry and thermocouple measurements. This paper analyses the effect of buoyancy when the wake of the cylinder is 3D and fully turbulent. Within this investigation the Reynolds number was chosen to be 1000 and the Richardson number is taken as 2.77 and 0 for comparison with the isothermal case. Results show that buoyancy effects strongly disturb the wake which becomes asymmetric and undergoes an upward deflection. Flow visualizations show the presence of two kinds of structures in the wake with heating of the cylinder. At the rear of the cylinder, the ambient fluid is subject to a high buoyant force due to the great temperature gradients. These significant gradients allow typical mushroom-like structures to emerge in the near wake region but also several diameters downwards the cylinder. In the lower shear-layer, heating is responsible of the generation of Kelvin-Helmholtz instabilities that usually exist at higher Reynolds numbers under isothermal conditions. Moreover comparison of velocity and temperature fields exhibits an opposite behaviour between velocity and temperature fluctuations in the free shear-layers.